Pendampingan Penyusunan Laporan Keuangan, Perpajakan Pada Semua Sekolah Muhammadiyah di Kabupaten Gresik - Suwarno Suwarno; Mu’minatus Sholikah; Umaimah Umaimah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
ABSTRACT The purpose of this service program is to provide knowledge and skills to schools so that they are able to prepare financial reports according to generally accepted accounting principles and are able to report tax obligations in accordance with applicable regulations. This activity was attended by 140 Muhammadiyah schools throughout Gresik Regency. The results obtained are that the school has obtained a decree ratifying the permit for the establishment of Muhammadiyah Charity Business from the Muhammadiyah Central Executive, the school has registered NPWP as the center to fulfill tax obligations, and the school has started to build an accounting system to produce school financial reports in accordance with accepted accounting General principles